SEG Technical Program Expanded Abstracts 2013 2013
DOI: 10.1190/segam2013-1131.1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation compensation in least-squares reverse time migration using the visco-acoustic wave equation

Abstract: Strong subsurface attenuation leads to distortion of amplitudes and phases of seismic waves propagating inside the earth. Conventional acoustic reverse time migration (RTM) and least-squares reverse time migration (LSRTM) do not account for this distortion, which can lead to defocusing of migration images in highly attenuative geologic environments. To correct for this distortion, we used a linearized inversion method, denoted as Q p -LSRTM. During the leastsquares iterations, we used a linearized viscoacousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These problems are severe when there is strong attenuation that leads to strong phase delays in the arrivals (Tarantola, 1988; Aki and Richards, 2002;Zhu and Harris, 2015;Komatitsch et al, 2016). To solve these problems, it is necessary to take the attenuation factor into account when applying WT to near-surface data (Dutta and Schuster, 2014). With the stronger computational ability, to understand the attenuation in both theory and practice becomes more feasible to exploration seismologists.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…These problems are severe when there is strong attenuation that leads to strong phase delays in the arrivals (Tarantola, 1988; Aki and Richards, 2002;Zhu and Harris, 2015;Komatitsch et al, 2016). To solve these problems, it is necessary to take the attenuation factor into account when applying WT to near-surface data (Dutta and Schuster, 2014). With the stronger computational ability, to understand the attenuation in both theory and practice becomes more feasible to exploration seismologists.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on this approximation, the velocity c is a function of ratio between the frequency ω and the reference frequency ω0. As a result, higher frequency components of seismic waves are attenuated more than low frequency components during the propagation (Dutta and Schuster, 2014). If Q >> 100, the attenuation can almost be neglected and c ≈ c0 holds except for very low or very high frequencies according to equation 17.…”
Section: Sensitivity Of the Velocity With Respect To Qmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1(a) and 1(c) show the true velocity and Q p models, respectively, used for generating the observed data with attenuation. The migration velocity model is shown in Figure 1(b) and the migration Q p model used for Q p -LSRTM (Dutta et al, 2013) is shown in Figure 1 The Q p -LSRTM image, shown in Figure 2(c), shows significant improvements in the image quality in the shallow and deeper parts. However, Q p -LSRTM is computationally expensive and it requires an estimate of the smoothly varying Q p distribution in the subsurface.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…However, a LSM method can be formulated that can partly account for attenuation loss if the Q-distribution is known (Dutta et al, 2013). If the modeling operator L accounts for attenuation, then the Hessian inverse [L T L] −1 estimated by iterative LSM partly compensates for the effects of attenuation suffered by the observed data d. This requires an accurate estimate of the attenuation model as well as modeling and adjoint operators that account for anelastic effects (Blanch and Symes, 1995;Dutta et al, 2013). Figure 3 shows the migration images for the Marmousi model with attenuation.…”
Section: Benefits Of Lsmmentioning
confidence: 99%